Risk-taking behaviour and executive functions, a major component of the risk of fall factors after recent stroke - Alain P. Yelnik; Ines Dekimèche; Emna Jelili; Ioannis Bargiotas; Marylène Jousse; Johann Beaudreuil; Alexis Schnitzler (Medical Journals Sweden, 2024)
Objective: This study investigated the weight of different cognitive disorders on patient behaviour influencing the risk of falls after recent stroke. Design: Survey and retrospective monocentric study. Subjects/patients: 74 professionals/108 patients. Methods: Survey of professionals to ask for their thoughts concerning the weight of different cognitive disorders on the risk of falls and a retrospective study of patients post-stroke to determine whether these cognitive deficits could distinguish fallers from non-fallers. Univariate and multivariate logistic regression analyses were conducted. Results: In part 1, major cognitive disorders identified were anosognosia, confusion, inattention, precipitation, and unilateral spatial neglect. In part 2, 25 patients (23%) were fallers. After adjustment for length of rehabilitation stay and disease severity, on multivariate analysis, the cognitive disorders significantly associated with risk of falls were anosognosia (odds ratio 16), precipitation (13.3), inattention (8.3), and perseveration (4.9). Unilateral spatial neglect was not independently associated. Aphasia did not play a role. Conclusion: Some cognitive disorders, easily identified before any neuropsychological assessment, strongly modify patient behaviour in terms of risk of falls. It is proposed that these disorders should not be considered as an additional factor along with physical and general factors but rather as a multiplying factor applied to the others.